Physical Education as a colonial and neoliberal category: transiting towards the thinking of human motricity in and from Abya Yala (Agora for Physical Education and Sport, 2021)
In this article we present a critique of the Chilean and Latin American educational system from the concepts of neoliberalism and modernity as a civilizing project focused on the denial of otherness. From there we justify the impossibility of a Physical Education that, as physical, separates, excludes and denies the various ways of living. We end up proposing human motricity as an ontological and epistemological alternative, understood as the capacity-condition of making-the world, from which it is possible to think about the educational.
Keywords: Physical Education; human motricity; modernity; Abya Yala; neoliberalism